Rate fears gauges and the dynamics of fixed income and equity volatilities - Mele, Antonio; Obayashi, Yoshiki; Shalen, Catherine (Journal of Banking & Finance, 2015)
While CBOE’s VIX index is widely acknowledged as a broad-based investor “fear gauge” for its strong inverse relationship with major equity indexes, one cannot necessarily expect it to translate to the level of future turbulence or investor risk-aversion in fixed-income markets. Indeed, expected volatilities in equity and interest rate markets as measured respectively by CBOE’s VIX and their newly launched swap rate volatility index, the SRVX, exhibit significantly distinct behavior. The two indexes react to different events and risk factors, thereby providing investors with complementary diversification, hedging, and risk-taking tools.